Conocimientos del profesional de enfermería en el manejo del paciente con trauma en el Hospital General Teófilo Dávila. - Carrión Ojeda, María José (2018)
According to the OMS, trauma is defined as a bodily injury to the organic level abruptly by external agents, trauma represents a public health problem, it constitutes the first cause of mortality, being the traffic, labor and domestic accidents that originate this type of affectations; The first ones cause the majority of pathologies of traumatic origin, causing around 1.8 million deaths worldwide between 20 and 50 million injuries after trauma and more than 5 million of permanent disabled. The present investigation with qualitative and quantitative focus, of a descriptive and transversal type, had as general objective to determine the level of knowledge of the Nursing professionals of the Teófilo Dávila General Hospital about the management of patients with trauma, for which a survey was applied to the professionals that work in the Emergency, Traumatology, Surgery, Surgical Center and the intensive care unit, whose results indicated that the female sex predominated in 87.7%, the age between 30 to 39 years, 41.1% of the professionals that work in the Emergency service, the 44.2% have job stability, the duration of 1 to 9 years in 54.8%, 75.3% have a third level academic training, 65.8% have training. In conclusion, 39.7% of the professional nursing staff of the General Hospital "Teófilo Dávila" has a medium level of knowledge in the management of the patient with trauma, with correct answers of 11 to 17 questions in the survey. KEYWORDS: Nursing management, trauma, knowledge.